PENGARUH FAKTOR-FAKTOR LINGKUNGAN CONCURRENT ENGINEERING TERHADAP KINERJA PENGEMBANGANPRODUK : STUDI EMPIRIS PADA INDUSTRI MANUFAKTUR DI INDONESIA - Natsir, Muh (Jurnal Analisis Bisnis Ekonomi, 2006)
The objective of this research was to study the effect of Concurrent Engineering environmental factors and product development performance that measured by overall variablesof financial performance. Using multiple regression to test the effect simultaneously and using simple regression to test the environmental factors of Concurrent Engineering effect on financial performance, operational performance and on overall performance. The result of data analysis found that all environmental factors of Concurrent Engineering effect individually didn’t influence financial performance, but simultaneously influenced financial performance 9,8%. Organizational factor communicate infastructure factors and products development factor individually didn’t influence operational performance. Customer requirements factors negatively influences operational performance and strategic integration factor positively influenced operational peformance. Simultaneously all Concurrent factor, communication infrastructure factor and product development factor individually didn’t influence overall product development performance. Customer requirements factor negatively influenced overall product development performance andstrategic integration factor positively influenced overall product development prformance. Simultaneously all Concurrent engineering enviromnetal factors didn’t have effect on overal product development performance.